Analysis of the Inconel 718 properties after roller burnishing - Casarin, Samuel José [UNESP]; de Godoi, Eduardo Luiz; de Angelo Sanchez, Luiz Eduardo [UNESP]; de Alcântara, Anne Caroline Melo [UNESP]; Gonçalves, Aparecido Carlos [UNESP] (Inderscience Publishers, 2022)
Experimental studies were performed to investigate the influence of roller burnishing (RB) parameters, as the temperature and the number of RB operations, on the subsurface microstructures and microhardness, surface roughness and roundness deviation of the Inconel 718 alloy. The experimental results indicate that the RB enhance the surface quality, reduces the surface roughness by 76.7% and increase the microhardness by 20.9% compared to the turned part. RB affects the microstructural morphology of the subsurface grains and improves roundness deviation of Inconel 718 parts. The presence of precipitates in the plastic deformation zone contributes to increase the mechanical strength of the subsurface. The RB operation, both at room temperature and at 310°C, proved to be very efficient in reducing the surface roughness of the Inconel 718. About roundness deviation, the increase of the RB temperature induces a greater specimen roundness deviation, and the hot RB operation is not favourable to improve the circularity of the specimen.
Keywords: Inconel 718; microstructure; roller burnishing